A composite soft magnetic material and preparation method thereof
By adding oxides such as cobalt oxide, cobalt oxide, and cobalt tetroxide in different valence states into the manganese-zinc ferrite soft magnetic material, the problem of loss of the manganese-zinc ferrite soft magnetic material in high-frequency applications is solved, and a more efficient solution is achieved. Low power loss and improved high frequency performance.
Patent Information
- Application Number
- CN202410818726.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-06-24
AI Technical Summary
The existing manganese-zeb ferrite soft magnetic materials have loss problems in high-frequency applications, limiting their performance in high-frequency applications.
By adding different price oxides such as cobalt oxide, cobalt oxide, and tetralet oxidation, mangible manganese zinc and iron oxygen soft magnetic materials are mixed to increase the resistivity of the material, reduce micro -defects, and improve the problem of stress concentration.
It effectively reduces the primary and secondary losses of the material at high frequencies and improves the high-frequency performance of the material.
Smart Images

Figure BDA0004908511370000051
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ferrite magnetic materials, and more specifically, relates to a composite soft magnetic material and a preparation method thereof. Background Art
[0002] Manganese-zinc ferrite is a soft magnetic material, which belongs to a type of ferrite magnetic material. This material is widely used in the fields of electronics and electrical engineering due to its high magnetic permeability, low loss, good temperature stability and cost-effectiveness.
[0003] The manufacture of manganese-zinc ferrites typically involves mixing manganese, zinc, iron and other possible additives, followed by a high-temperature sintering process to form a ceramic material with the desired magnetic properties.
[0004] By optimizing the ratio of manganese, zinc and other elements, the properties of manganese-zinc ferrite can be optimized to meet the needs of specific applications. For example, increasing the zinc content can increase the magnetic permeability, while increasing the manganese content can improve the saturation magnetization of the material.
[0005] However, with the continuous iteration of technology and the increase in demand, manganese-zinc ferrite materials still face some technical challenges in practical applications, such as loss problems in high-frequency applications: In high-frequency signal processing, manganese-zinc ferrite needs to have extremely low power loss to ensure its high efficiency. However, as the frequency increases, the loss of the material may increase, which limits its performance in high-frequency applications. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the loss problem of the existing manganese-zinc ferrite soft magnetic material in high-frequency applications, and provide a composite soft magnetic material and a preparation method thereof.
[0007] The purpose of the present invention is to provide a composite soft magnetic material.
[0008] Another object of the present invention is to provide a method for preparing the composite soft magnetic material.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A method for preparing a composite soft magnetic material, the specific preparation steps comprising:
[0011] According to the molar ratio, 52-54 parts of iron oxide, 16-20 parts of zinc oxide, 30-35 parts of manganese oxide, 0.01-0.012 parts of cobalt oxide, 0.015-0.016 parts of cobaltous oxide, and 0.008-0.012 parts of tricobalt tetroxide are taken in sequence;
[0012] After the above components are ball-milled and mixed evenly, they are dried to remove moisture;
[0013] Pressing the dried material into a desired shape of blank;
[0014] The green body is placed in a nitrogen atmosphere at a temperature of 1300-1350° C. for 2-4 hours, and then cooled and discharged to obtain a composite soft magnetic material.
[0015] The above technical scheme dopes and modifies the manganese-zinc ferrite soft magnetic material by adding oxides of different valence states of the Co element, specifically, three oxides of cobalt oxide, cobaltous oxide and cobalt tetroxide; firstly, the cobalt element in the three oxides of different valence states can present different electronic structures and oxidation states, and a certain amount of the three added is matched, which can increase the resistivity of the material at the grain boundary, thereby affecting the current flow, which helps to reduce eddy current losses; and, with the assistance of microwave sintering, the three can effectively reduce microscopic defects in the material, such as pores and impurities, to avoid these defects causing additional energy loss at high frequencies.
[0016] In addition, the inventors found that three oxides with different valence states can effectively improve the stress concentration inside the material during high-temperature sintering, and effectively release the stress at the grain boundaries, thereby reducing the loss problem caused by the existence of stress under high-frequency conditions.
[0017] Furthermore, the specific preparation step also includes: before the ball milling mixing, adding cobalt tetroxide and an equal mass of nickel oxide.
[0018] By further adding nickel oxide, after the addition of nickel oxide, cobalt oxides in different valence states can more easily participate in the chemical composition and crystal structure of the material with other materials, thereby affecting the magnetization process and loss mechanism, and further improving the loss of the product under high-frequency conditions.
[0019] Furthermore, the ball milling and mixing uniformly includes: adding ball milling beads according to a ball-to-material mass ratio of 35:1-40:1, and continuously ball milling and mixing for 6-8 hours at a rotation speed of 400-450r / min and a revolution speed of 500-550r / min.
[0020] Furthermore, the ball milling mixing also includes: adding 0.3% of the mass of polytetrafluoroethylene in the ball mill; the mass of the main material in the ball mill is the sum of the mass of the iron oxide, the zinc oxide, and the manganese oxide.
[0021] Furthermore, the compression molding includes: pressing for 35-45 seconds at a pressure of 120-130 MPa.
[0022] By adjusting the ball milling process parameters and further selecting specific pressing conditions during the pressing process, the components can be effectively and evenly mixed, pressed to a certain density, and then matched with a certain microwave sintering process, so that the components can be quickly and effectively sintered to form a whole, and the internal defective structure can be eliminated, further reducing the energy loss under high-frequency conditions.
[0023] Further, the iron oxide has a D50 of 15-20 nm, the zinc oxide has a particle size of 35-40 nm, the manganese oxide has a D50 of 25-30 nm, the cobalt oxide has a D50 of 3-5 nm, the cobaltous oxide has a D50 of 3-5 nm, and the cobaltous oxide has a D50 of 3-5 nm.
[0024] Furthermore, the D50 of the nickel oxide is 3-5 nm.
[0025] Oxides of different sizes are selected for doping, so that under the above-mentioned processing conditions, the components can effectively diffuse and flow inside, thereby improving the uniformity of their mixing, thereby improving the stress concentration problem in different parts, reducing product defects, and ultimately reducing the high-frequency energy loss of the product.
[0026] A composite soft magnetic material is prepared by adopting the composite soft magnetic material preparation method. DETAILED DESCRIPTION
[0027] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0028] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0029] Example 1
[0030] According to the molar ratio, 52 parts of iron oxide, 16 parts of zinc oxide, 30 parts of manganese oxide, 0.01 parts of cobalt oxide, 0.015 parts of cobaltous oxide, 0.008 parts of cobalt tetroxide are taken in sequence; and the same mass of nickel oxide as the cobalt tetroxide;
[0031] The D50 of the iron oxide is 15 nm, the particle size of the zinc oxide is 35 nm, the D50 of the manganese oxide is 25 nm, the D50 of the cobalt oxide is 3 nm, the D50 of the cobaltous oxide is 3 nm, the D50 of the cobalt oxide is 3 nm, and the D50 of the cobalt oxide is 3 nm; the D50 of the nickel oxide is 3 nm;
[0032] The iron oxide, the zinc oxide, the manganese oxide, the cobalt oxide, the cobaltous oxide, the cobaltous oxide, the cobaltous oxide and the nickel oxide are mixed and poured into a ball mill, and then 0.3% of the mass of polytetrafluoroethylene in the ball mill is added; the mass of the main material in the ball mill is the sum of the masses of the iron oxide, the zinc oxide and the manganese oxide; then, ball milling beads are added according to a ball-to-material mass ratio of 35:1, and the ball milling is continued for 6 hours at a rotation speed of 400 r / min and a revolution speed of 500 r / min; wherein, the ball-to-material mass ratio is the sum of the mass of the ball milling beads and the mass of all other raw materials in the ball mill except the ball milling beads; after the ball milling is completed, the material is discharged to obtain the ball mill material;
[0033] The obtained ball mill material is then transferred into an oven and dried to a constant weight at 95°C to obtain a dry ball mill material;
[0034] The obtained dried ball mill material was transferred to a mold and filled, and then pressed for 35 seconds under a pressure of 120 MPa to obtain a green body of the desired shape;
[0035] The green body is then transferred into a sintering furnace, and heated to 1300°C at a heating rate of 10°C / min in a nitrogen atmosphere. After high-temperature sintering for 2 hours, the green body is cooled to room temperature and discharged to obtain a composite soft magnetic material.
[0036] Example 2
[0037] According to the molar ratio, 53 parts of iron oxide, 18 parts of zinc oxide, 32 parts of manganese oxide, 0.011 parts of cobalt oxide, 0.015 parts of cobaltous oxide, 0.01 parts of cobalt tetroxide, and nickel oxide of the same mass as the cobalt tetroxide are taken in sequence;
[0038] Among them, the D50 of the iron oxide is 18nm, the particle size of the zinc oxide is 36nm, the D50 of the manganese oxide is 27nm, the D50 of the cobalt oxide is 4nm, the D50 of the cobaltous oxide is 4nm, the D50 of the cobalt trioxide is 4nm; the D50 of the nickel oxide is 4nm;
[0039] The iron oxide, the zinc oxide, the manganese oxide, the cobalt oxide, the cobaltous oxide, the cobaltous oxide, the cobaltous oxide and the nickel oxide are mixed and poured into a ball mill, and then 0.3% of the mass of polytetrafluoroethylene in the ball mill is added; the mass of the main material in the ball mill is the sum of the masses of the iron oxide, the zinc oxide and the manganese oxide; then, ball milling beads are added according to a ball-to-material mass ratio of 38:1, and the ball milling is continued for 7 hours at a rotation speed of 420 r / min and a revolution speed of 530 r / min; wherein, the ball-to-material mass ratio is the sum of the mass of the ball milling beads and the mass of all other raw materials in the ball mill except the ball milling beads; after the ball milling is completed, the material is discharged to obtain the ball milling material;
[0040] The obtained ball mill material is then transferred into an oven and dried to a constant weight at 95°C to obtain a dry ball mill material;
[0041] The obtained dried ball mill material was transferred to a mold for filling, and then pressed for 40 seconds under a pressure of 125 MPa to obtain a green body of the desired shape;
[0042] The green body was transferred into a sintering furnace, and heated to 1320°C at a heating rate of 10°C / min in a nitrogen atmosphere. After high-temperature sintering for 3 hours, the green body was cooled to room temperature and discharged to obtain a composite soft magnetic material.
[0043] Example 3
[0044] According to the molar ratio, 54 parts of iron oxide, 20 parts of zinc oxide, 35 parts of manganese oxide, 0.012 parts of cobalt oxide, 0.016 parts of cobaltous oxide, 0.012 parts of cobalt tetroxide are taken in sequence; and nickel oxide of the same mass as the cobalt tetroxide is taken;
[0045] Among them, the D50 of the iron oxide is 20nm, the particle size of the zinc oxide is 40nm, the D50 of the manganese oxide is 30nm, the D50 of the cobalt oxide is 5nm, the D50 of the cobaltous oxide is 5nm, the D50 of the cobaltous oxide is 5nm, and the D50 of the cobalt oxide is 5nm; the D50 of the nickel oxide is 5nm;
[0046] The iron oxide, the zinc oxide, the manganese oxide, the cobalt oxide, the cobaltous oxide, the cobaltous oxide, the cobaltous oxide and the nickel oxide are mixed and poured into a ball mill, and then 0.3% of the mass of polytetrafluoroethylene in the ball mill is added; the mass of the main material in the ball mill is the sum of the masses of the iron oxide, the zinc oxide and the manganese oxide; then, ball milling beads are added at a ball-to-material mass ratio of 40:1, and the ball milling is continued for 8 hours at a rotation speed of 450 r / min and a revolution speed of 550 r / min; wherein, the ball-to-material mass ratio is the sum of the mass of the ball milling beads and the mass of all other raw materials in the ball mill except the ball milling beads; after the ball milling is completed, the material is discharged to obtain the ball mill material;
[0047] The obtained ball mill material is then transferred into an oven and dried to a constant weight at 95°C to obtain a dry ball mill material;
[0048] The obtained dried ball mill material was transferred to a mold for filling, and then pressed for 45 seconds under a pressure of 130 MPa to obtain a green body of the desired shape;
[0049] The green body is then transferred into a sintering furnace, and heated to 1350°C at a heating rate of 10°C / min in a nitrogen atmosphere. After high-temperature sintering for 4 hours, the green body is cooled to room temperature and discharged to obtain a composite soft magnetic material.
[0050] Example 4
[0051] The present embodiment differs from the embodiment 1 in that an equal mass of tin oxide is used to replace nickel oxide, and other conditions remain unchanged.
[0052] Example 5
[0053] The present embodiment differs from the embodiment 1 in that nickel oxide is not added and the other conditions remain unchanged.
[0054] Example 6
[0055] Compared with Example 1, the present embodiment is different in that: the D50 of the iron oxide is 15 nm, the particle size of the zinc oxide is 35 nm, the D50 of the manganese oxide is 25 nm, the D50 of the cobalt oxide is 15 nm, the D50 of the cobaltous oxide is 13 nm, the D50 of the cobaltous oxide is 12 nm; the D50 of the nickel oxide is 15 nm; and the other conditions remain unchanged.
[0056] Comparative Example 1
[0057] The difference between this comparative example and Example 1 is that cobalt oxide, cobalt trioxide and nickel oxide are not added, and other conditions remain unchanged.
[0058] Comparative Example 2
[0059] The difference between this comparative example and Example 1 is that cobaltous oxide, cobalt trioxide and nickel oxide are not added, and other conditions remain unchanged.
[0060] Comparative Example 3
[0061] The difference between this comparative example and Example 1 is that cobalt oxide, cobaltous oxide and nickel oxide are not added, and other conditions remain unchanged.
[0062] The performance tests were performed on the products obtained in Examples 1-6 and Comparative Examples 1-3. The specific test methods and test results are as follows:
[0063] At a temperature of 100°C, the power loss of the sample was tested at 1MHz30mT and 3MHz10mT using the SY-8232B-H analyzer from Iwasaki, Japan. The specific test results are shown in Table 1:
[0064] Table 1: Product performance test results
[0065]
[0066] It can be seen from the test results in Table 1 that the product obtained by the present invention has relatively lower power loss under high temperature conditions.
[0067] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a composite soft magnetic material, characterized in that: The specific preparation steps include: According to the molar ratio, 52-54 parts of iron oxide, 16-20 parts of zinc oxide, 30-35 parts of manganese oxide, 0.01-0.012 parts of cobalt oxide, 0.015-0.016 parts of cobaltous oxide, and 0.008-0.012 parts of tricobalt tetroxide are taken in sequence; After the above components are ball-milled and mixed evenly, they are dried to remove moisture; Pressing the dried material into a desired shape of blank; The green body is placed in a nitrogen atmosphere at a temperature of 1300-1350° C. for 2-4 hours, then cooled and discharged to obtain a composite soft magnetic material; The D50 of the iron oxide is selected to be 15-20nm, the particle size of the zinc oxide is 35-40nm, the D50 of the manganese oxide is 25-30nm, the D50 of the cobalt oxide is 3-5nm, the D50 of the cobaltous oxide is 3-5nm, and the D50 of the cobaltous oxide is 3-5nm.
2. The method for preparing a composite soft magnetic material according to claim 1, characterized in that: The specific preparation steps also include: before the ball milling mixing, adding cobalt tetroxide and the same mass of nickel oxide.
3. The method for preparing a composite soft magnetic material according to claim 1, characterized in that: The ball milling and mixing uniformly comprises: adding ball milling beads according to a ball-to-material mass ratio of 35:1-40:1, and continuously ball milling and mixing for 6-8 hours at a rotation speed of 400-450 r / min and a revolution speed of 500-550 r / min.
4. The method for preparing a composite soft magnetic material according to claim 3, characterized in that: The ball milling mixing also includes: adding polytetrafluoroethylene which accounts for 0.3% of the mass of the main material in the ball mill; the mass of the main material in the ball mill is the sum of the mass of the iron oxide, the zinc oxide and the manganese oxide.
5. The method for preparing a composite soft magnetic material according to claim 4, characterized in that: The compression molding comprises: pressing for 35-45 seconds at a pressure of 120-130 MPa.
6. The method for preparing a composite soft magnetic material according to claim 2, characterized in that: The D50 of the nickel oxide is 3-5 nm.
7. A composite soft magnetic material, characterized in that: The composite soft magnetic material is prepared by the method for preparing the composite soft magnetic material according to any one of claims 1 to 6.
Citation Information
Patent Citations
Manganese-zinc low-power-loss ferrite material applied at high frequency and preparation method thereof
CN113292328A
Anti-bias and anti-drop iron-poor manganese zinc ferrite material and preparation method thereof
CN116891377A